Assessing the Impact of Large-Scale Trends on Ontario's Pedestrian Fatality Rate. Issue 8 (August 2021) - Plonka, Sarah C.; Volo, Sara; Byrne, Patrick A.; Sinclair, Ian; Prabha, Thadsha
Pedestrian-involved collisions are a key contributor to roadway fatalities in Ontario; pedestrian deaths have been growing as a proportion of total road fatalities. This study aimed first to determine trends in the pedestrian fatality rate in Ontario over time and, second, to assess the impact of select large-scale trends on pedestrian fatalities. Large-scale trends were identified through a review of the literature and hypotheses were tested using Ontario collision data from 2002 to 2016. The following four key areas were assessed for their impact: (1) the aging demographic; (2) the impact of increasing consumer preference for light trucks; (3) the potential for an increase in alcohol-consuming pedestrians associated with a decrease in alcohol-consuming drivers, and; (4) increasing inattention, caused, in part, by pedestrians and drivers using electronic devices. A quadratic model, with a minimum at 2010, best described changes in Ontario's pedestrian fatality rate, suggesting a transition from a decreasing to increasing trend at that time. Results of the four key areas were: (1) the proportion of pedestrians aged 75 and older being killed has been increasing over time, a trend that can be fully explained by their increased representation in Ontario's population, a trend which is expected to continue; (2) similarly, the increase in the proportion of pedestrians killed by a light truck can be explained by their increased representation in Ontario's registered vehicle population; (3) the odds of a pedestrian being alcohol positive have been decreasing over time; and (4) the odds are higher that a driver who kills a pedestrian is inattentive.